2007
DOI: 10.1021/bi602459v
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Structural Features of Hydantoin Lesions Translate into Efficient Recognition by Escherichia coli Fpg

Abstract: Oxidation of guanine (G) and 8-oxoguanine (OG) with a wide variety of oxidants yields the hydantoin lesions, guanidinohydantoin (Gh) and spiroiminodihydantoin (Sp). These two lesions have garnered much recent attention due to their unusual structures and high mutagenic potential. We have previously shown that duplexes containing Gh and Sp are substrates for the base excision repair glycosylase Escherichia coli Fpg (EcFpg). In order to evaluate the recognition features of these unusual lesions, binding and foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 72 publications
3
54
0
Order By: Relevance
“…S4) suggested that although MmuNeil3Δ324 is bifunctional (with rates of 0.119AE 0.016 min −1 for single-stranded Sp1 and 0.053 AE 0.002 min −1 for double-stranded Sp1 substrates), its lyase activity is not coupled to its glycosylase activity, since the slow lyase reaction of MmuNeil3Δ324 does not limit the enzyme turnover of the glycosylase reaction. MmuNeil3Δ324 has a similar catalytic turnover rate for the glycosylase reaction (3.2 min −1 , Table 1) on double-stranded Sp substrate as does E. coli Nei (1.6-13.0 min −1 (22)(23)(24)) and Fpg (6.0-34.2 min −1 (22)(23)(24)) proteins, although it is much slower than NEIL1 (177 min −1 (25)) on the same substrate. However, MmuNeil3Δ324 exhibits a much higher binding affinity to a double-stranded Sp substrate (K m ¼ 0.753 nM, Table 1), compared to EcoFpg (K m ¼ 25 nM (24)) and EcoNei (K m ¼ 30 nM (24)).…”
Section: Resultsmentioning
confidence: 97%
“…S4) suggested that although MmuNeil3Δ324 is bifunctional (with rates of 0.119AE 0.016 min −1 for single-stranded Sp1 and 0.053 AE 0.002 min −1 for double-stranded Sp1 substrates), its lyase activity is not coupled to its glycosylase activity, since the slow lyase reaction of MmuNeil3Δ324 does not limit the enzyme turnover of the glycosylase reaction. MmuNeil3Δ324 has a similar catalytic turnover rate for the glycosylase reaction (3.2 min −1 , Table 1) on double-stranded Sp substrate as does E. coli Nei (1.6-13.0 min −1 (22)(23)(24)) and Fpg (6.0-34.2 min −1 (22)(23)(24)) proteins, although it is much slower than NEIL1 (177 min −1 (25)) on the same substrate. However, MmuNeil3Δ324 exhibits a much higher binding affinity to a double-stranded Sp substrate (K m ¼ 0.753 nM, Table 1), compared to EcoFpg (K m ¼ 25 nM (24)) and EcoNei (K m ¼ 30 nM (24)).…”
Section: Resultsmentioning
confidence: 97%
“…EcFpg utilizes an N-terminal proline to catalyze base removal and β,δ-elimination reactions to yield a strand break. This work led to a follow-up paper with greater details about the repair process in a 30-mer duplex leading to many key observations [188]. Diastereomeric mixtures of each hydantoin were studied opposite all four canonical nucleotides to determine whether Sp or Gh were removed by EcFpg as efficiently as the signature substrate OG:C. When Sp or Gh were base paired with A they were operated on by EcFpg more efficiently than an OG:C base pair, and when the hydantoins were opposite C, T, or G they were nearly as good substrates as OG:C. One key point in comparisons between the 18-mer and 30-mer duplex studies is that the duplex length is critical to capturing a true snapshot of the removal kinetics for highly disruptive lesions like the hydantoins in dsDNA.…”
Section: The Hydantoins Are Substrates For Ecfpg Ecnei and Neil1mentioning
confidence: 99%
“…The hydantoin lesions, Gh and Sp have been shown to be substrates for the E. coli enzymes Fpg (24,39) and Nei (40), and the murine enzymes NEIL1 and NEIL2 (38). In order to elucidate 1 Abbreviations: BER, base excision repair; bp, base pair; EDTA, ethylenediaminetetraacetic acid; Fpg/MutM; bacterial formamidopyrimidine glycosylase; Gh, guanidinohydantoin; hNEIL1, human Nei-like glycosylase 1; Nei; endonuclease VIII; NTH1, endonuclease III homologue 1; OG, 7,8-dihydro-8-oxoguanine; 5-OHC, 5-hydroxycytosine; PAGE, polyacrylamide gel electrophoresis; ROS, reactive oxygen species, Sp, spiroiminodihydantoin; Tg, thymine glycol.…”
mentioning
confidence: 99%